Indisciplina escolar: relatos de professores e pais de alunos dos anos iniciais do ensino fundamental de escolas do município de Parintins-AM - Simas, Thyeyda Gretchen da Silva (Brasil, 2022)
This study aimed to analyze indiscipline in the school context from the perspective of teachers and parents of students in the early years of elementary school in public schools in Parintins - AM. And specific objectives: To know the view of teachers and parents of students on the causes and consequences of school indiscipline; Identify educational actions and the teacher's role in confronting school indiscipline; To describe how the indiscipline of the students affects the teaching-learning process. The qualitative approach research is based on the studies of Aquino (1998); Belém (2008); France (1996); Giancaterino (2007); Oliveira, Santos and Mendes (2010); Parrat-Dayan (2008), among other scholars. The study took place from 2018 to 2021, with 06 teachers from the early years of Elementary School and 11 parents of students as subjects, but only 08 responded to the questionnaire. The data collection instruments were: letters written by teachers and questionnaires applied to students' parents via WhatsApp. The results show that, on a daily basis, both teachers and students deal with school indiscipline. Thus, dialogue is the first action, the main way to face indiscipline at school, therefore, dialogic communication between parents, teachers and students, as well as the continuing education of teachers, becomes important, as it opens space for discussions, readings, re-readings and analyzes about issues involving school indiscipline.